Prevalence and clinical characterisation of thyroid dysfunction in COPD: a systematic review and meta-analysis - Ling Wu; Li He; Xiaorong Hu; Hanqiong Zhang; Zeming He; Xiaotao Huang; Caihong Li; Yong Zhang (Frontiers in Medicine)
BackgroundThe prevalence of COPD is increasing annually, accompanied by a growing number of complications and organ function abnormalities. Thyroid dysfunction is prevalent among patients with chronic obstructive pulmonary disease (COPD). Updated evidence is needed to complement previous systematic reviews on this topic to provide best practice.MethodsThe EMBASE, Web of Science, Cochrane and PubMed databases were searched for articles containing the keywords “COPD” and “thyroid dysfunction” (PROSPERO CRD42024592606). Eligibility screening, data extraction and quality assessment of retrieved articles were performed independently by two reviewers. Meta-analyses were performed to determine the prevalence of thyroid dysfunction in patients with COPD. Regression analyses were used to explore sources of heterogeneity. The clinical features of COPD combined with thyroid dysfunction were clarified by comparing the age, sex (percentage of males), BMI, smoking index, Forced Vital Capacity (FVC%), Forced Expiratory Volume in One Second (FEV1%), partial pressure of oxygen (PaO2), partial pressure of carbon dioxide (PaCO2), and albumin in patients with and without thyroid dysfunction. The differences in the prevalence of thyroid dysfunction between stable and acute exacerbations in COPD were also compared.ResultsTwelve studies were included, with an overall prevalence of 42.1% (95% CI, 31.8–52.9). The most common type of thyroid dysfunction in COPD was non-thyroidal illness syndrome (NTIS) in 45.3% (95% CI, 22.3–68.3). There was no difference in the prevalence of dysfunctions between stable and acute exacerbations of COPD. Patients in the thyroid dysfunction group in COPD had lower PCO2 and albumin and higher FEV1%.ConclusionThyroid dysfunction has a high prevalence among patients with COPD, with NTIS being the most common. Thyroid dysfunction in COPD may affect lung function and lead to decreased albumin. Patients with COPD should be screened for thyroid function, and attention should be paid to the clinical features of this group of patients with thyroid dysfunction to facilitate better identification and management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, PROSPERO ID (CRD42024592606).